The evolution of e-banking: a study of Indian and Kenyan technology awareness. (8th June 2009) - Nyangosi, Richard; Arora, J.S.; Singh, Sumanjeet
Banking through electronic channels has gained increasing popularity in recent years. This system, popularly known as 'e-banking', provides alternatives for faster delivery of banking services to a wide range of customers. This study aims to collect customers' opinions regarding the importance of e-banking and the adoption levels of various e-banking technologies in India and Kenya. The study also highlights the trends of e-banking indicators in India and Kenya. Further, it segregates the data collected into an Indian and a Kenyan customer basis, to identify differences in their attitudes towards the emergence of e-banking. The overall result indicates that customers in both countries have developed positive attitudes and they attach much importance to the emergence of e-banking.